Indonesian Government Policy in Protecting the Indonesian Diaspora in Mindanao, South Philippines - Mediawan. S, Sigit Danuansyah; Maksum, Ali (Budapest International Research and Critics University, 2022)
This article focuses on discussing the reasons for the Indonesian government to protect the Indonesian diaspora with the status of stateless people in the Southern Philippines. And also the efforts made by the Indonesian government in protecting Indonesians in the Southern Philippines Mindanao who does not yet have official citizenship status so that it will be difficult to get legal protection from the state. In addition, those who do not have citizenship will also find it difficult to travel anywhere because there is no official identity. So that makes them just settle and settle in a village and also have to survive during difficult economic conditions. The findings reveal that the government's reason for protecting the stateless Indonesian diaspora is because the Indonesian government has an interest in keeping the Indonesian diaspora as Indonesian citizens and so that the Indonesian diaspora can obtain their rights as human beings who have citizenship status. Efforts made by the government are trying to collect data immediately and issue free passports and ID cards for those who do not have citizenship status, provide free education as well as scholarships, educate society about natural resource management.